Faktor-Faktor yang Mempengaruhi Kinerja Pemasaran Pada Sentra Industri Kue dan Roti di Desa Bugo - Samsul Arifin (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to test empirically the effect of the independent variables of market orientation, learning orientation, and entrepreneurial orientation on the dependent variable of marketing performance in the cake and bakery industry centers, Bugo Village, Welahan District, Jepara Regency. This type of research used in this research is quantitative. The type of data in this research is primary data. The population of this research is the cake and bakery industrial centers in Bugo Village, Welahan District, Jepara yang Regency, totaling 96 people. The sampling technique uses probability sampling using the Slovin calculation formula. Hypothesis testing was carried out by distributing questionnaires to as many as 96 business owners of the cake and bread industry centers in Bugo Village, Welahan District, Jepara Regency. By using the multiple regression analysis methods, it can be concluded that partially market orientation, learning orientation, and entrepreneurial orientation have a positive and significant effect on the marketing performance of the cake and bakery industry centers in Bugo Village, Welahan District, Jepara Regency. Meanwhile, simultaneously it is concluded that the variables of market orientation, learning orientation, and orientation together have an influence on the dependent variable of marketing performance.